SELF REGULATED LEARNING (STUDY FOR STUDENTS REGULAR AND TRAINING) - Hafiz Hidayat; Puji Gusri Handayani (Jurnal Penelitian Bimbingan dan Konseling, 2018)
Self Regulated Learning (Study for regular and training students). This study aims to describe self regulated learning of regular students and training, and to test the difference of self regulated learning of regular and training class students.The samples used are 65 students of SMA N 5 Padang selected with purposive sampling and simple random sampling technique The instrument used is "Self Regulated Learning Scale" (SSRL) with reliability of 0.817.Research findings show that (1) self regulated learning of regular class students and training is quite good, (2) there are differences of self regulated learning of regular students with training class students, where regular class students have self-regulated learning better than the students of the training class. Keyword: Self Regulated Learning